2015
DOI: 10.1038/srep08507
|View full text |Cite
|
Sign up to set email alerts
|

Prejudiced interactions: implicit racial bias reduces predictive simulation during joint action with an out-group avatar

Abstract: During social interactions people automatically apply stereotypes in order to rapidly categorize others. Racial differences are among the most powerful cues that drive these categorizations and modulate our emotional and cognitive reactivity to others. We investigated whether implicit racial bias may also shape hand kinematics during the execution of realistic joint actions with virtual in- and out-group partners. Caucasian participants were required to perform synchronous imitative or complementary reach-to-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 57 publications
6
59
1
1
Order By: Relevance
“…Previous studies have shown that interactions impact on a number of higher-level perceptuocognitive representations as they change the way we co-represent the physical space [22], display our attention [54], perceive our partner [37,[72][73][74][75] and build a common representation of the task at hand [51]. Here, we expand this knowledge by showing that repeatedly interacting with a partner shapes the way in which the pair communicate and organize their behaviour by aligning their representation of the knowledge shared between individuals.…”
mentioning
confidence: 65%
“…Previous studies have shown that interactions impact on a number of higher-level perceptuocognitive representations as they change the way we co-represent the physical space [22], display our attention [54], perceive our partner [37,[72][73][74][75] and build a common representation of the task at hand [51]. Here, we expand this knowledge by showing that repeatedly interacting with a partner shapes the way in which the pair communicate and organize their behaviour by aligning their representation of the knowledge shared between individuals.…”
mentioning
confidence: 65%
“…Perception of these blended mocap stimuli could be tested in an adaptation context (de la Rosa et al ., 2016) or in the context of different facial identities (Ferstl, Bülthoff, & de la Rosa, 2017). Using a similar method, (Sacheli et al ., 2015) applied the same animation clip to virtual characters with different skin colours (white and black) and found that a stronger interference effect on participant's motion from an in‐group VC as compared to the outgroup one. These studies illustrate the value of using mocap and virtual character technology to create experimental stimuli with precise control.…”
Section: The Foothills – How To Use Vrmentioning
confidence: 99%
“…With virtual characters, it is possible to create infinitely many combinations of social variables and test them against each other. This has proved valuable in the study of social perception (Todorov, Said, Engell, & Oosterhof, 2008) and social interaction (Hale & Hamilton, 2016; Sacheli et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Whilst previous work has quantitatively examined the kinematic elements of imitative behavior in both healthy people (e.g., Braadbaart et al, 2012;Campione & Gentilucci, 2011;Era et al, 2018;Forbes & Hamilton, 2017;Gold et al, 2008;Hayes et al, 2016;Krüger et al, 2014;Pan & Hamilton, 2015;Reader & Holmes, 2015;Reader et al, 2018;Sacheli et al, 2012;Sacheli et al, 2013, Sacheli, Christensen, et al, 2015Wild et al, 2010;Williams et al, 2013) and brain-damaged patients (e.g., Candidi et al, 2018;Hermsdörfer et al, 1996), as far as we are aware no previous experiments have looked at so many components of the velocity profile in order to compare the coarse-grained (i.e., wrist) kinematic approach to meaningful and meaningless action imitation. Much informative work has been done to assess action performance in meaningful and meaningless action imitation (e.g., Buxbaum et al, 2014;Goldenberg & Hagmann, 1997;Mengotti et al, 2013), but frequently using only subjective rating measures.…”
Section: Kinematics In Meaningful and Meaningless Action Imitationmentioning
confidence: 99%